Development of an evidence-based framework for the prevention and management of musculoskeletal disorders in South Africa - De Bruyn, Elrico (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Background: Musculoskeletal Disorders (MSDs) are multi-causal soft tissue disorders that result in disability, discomfort, and pain. MSDs are prevalent in 21.5% of the world's population and carry a great financial and personal burden to individuals, businesses and countries alike. The multi-casual nature of MSDs has resulted in a vast amount of literature being published on how to prevent and manage the disorders, to the extent that navigating through the literature to find effective and context-specific interventions has become time-consuming and difficult. This is the case in South Africa, where ergonomists have no guide or framework to navigate MSD literature, and context-specific literature is limited. Aims: This study aimed to assist ergonomists in South Africa navigate the MSD literature to identify and select appropriate MSD prevention and management interventions. To do so, three objectives of the study were identified: 1. Review MSD literature to identify effective MSD prevention and management interventions. 2. Create a framework to act as a guide for ergonomists to navigate MSD prevention and management studies. 3. To verify the suitability of the framework in the South African context. To achieve these objectives, the study took a two-phased approach. Phase 1: A scoping review of MSD literature was conducted to identify effective MSD prevention and management approaches. Sixteen (n=16) prevention strategies and fourteen (n=14) management strategies were identified. The information from the review was analysed and grouped into five hierarchical levels of interventions ("Law" , "Organisational Policies" , "Management Systems" , Workplace Interventions" , and "Individual" ). This information, along with a conceptual model created for the navigation of the literature, was used to create a draft framework for musculoskeletal disorder prevention and management. It was concluded that although there were many effective MSD interventions, there was a lack of South African-specific literature. Phase 2: Interviews with five certified ergonomists working in the South African context were conducted to verify the framework's suitability for a South African working environment. The interviews identified two MSD prevention and three MSD management themes as effective in South Africa. Both prevention themes ("training and education" and "workplace interventions" ) were also mentioned to be part of the stakeholders' ideal MSD prevention programme, further reinforcing their usefulness. The use of "workplace interventions" was also identified to be effective in MSD management, alongside interventions at the management level and the use of alternative tools and equipment. However, the lack of managerial buy-in was identified as a barrier to MSD prevention. Stakeholders also highlighted that job specification and work hardening was an MSD strategy missing from the framework that was effective in South Africa's MSD management. The use of surveillance practices was found to be ineffective in South Africa, with lots of resistance towards it from workers. Conclusion: The framework presented in Phase 1 identified many effective MSD interventions; however, only a few were found to be applicable to the South African working context during Phase 2. Future research should focus on identifying the success of different MSD interventions in South Africa with participation from the ergonomists involved in the implementation to create an even more suitable guide that matches the South African ergonomist's needs.
Keywords: Musculoskeletal system Wounds and injuries -- South Africa; Musculoskeletal system Wounds and injuries Treatment; Human engineering Handbooks, manuals, etc.; Musculoskeletal system Wounds and injuries Prevention; Industrial engineering -- South Africa; Work environment -- South Africa